1989
DOI: 10.1149/1.2096784
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Li‐6 by Countercurrent Electromigration in Molten LiNO3

Abstract: High enrichment of 6Li was attempted by improvement a previously used countercurrent electromigration method in molten LiNO3. In order to prevent a possible outflow of Li § ions into a large cathode compartment which contained NH4NO3 melt by electromigration, a small zone of NaNO3 was formed between molten LiNO3 and NH4NO3 in a separation tube. The electromigration cell was reformed so that the temperature in the separation tube could be kept at an intended value. 6Li was enriched from 7.4 to 91.2% in 39 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This phenomenon is attributed to the smaller hydration radius, lower hydration energy, and higher ionic mobility of NH 4 + across the CMX membrane compared to Na + (Table 2 ). [ 17 , 36 , 37 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is attributed to the smaller hydration radius, lower hydration energy, and higher ionic mobility of NH 4 + across the CMX membrane compared to Na + (Table 2 ). [ 17 , 36 , 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is attributed to the smaller hydration radius, lower hydration energy, and higher ionic mobility of NH 4 + across the CMX membrane compared to Na + (Table 2). [17,36,37] In Additionally, Aliaskari and Schäfer [40] point out that the quality of the feed water, including contaminant concentration, pH and salinity, significantly influences contaminant removal during the ED process. For example, several studies have shown that nitrate removal is particularly high in the presence of NaCl, which can be explained by the high diffusion and ionic mobility of nitrates, as well as their competitive removal with other anions such as chloride, bicarbonate and fluoride.…”
Section: Feasibility Of Eliminating Ammonium Ions By Edmentioning
confidence: 99%